Parte orientale del Canadá, Nuova Scozia settentrionale, e parte di Labrador - Zatta, Antonio, fl. 1757-1797 ([Venice], 1778)
Hand coloured. Relief shown pictorially. Shows Quebec, including eastern portions named "Labrador" which are not part of modern-day Labrador, N.L. Also shows "Nuova Scozia" and "I.S. Giovanni," which correspond to New Brunswick and Prince Edward Island, respectively; the land mass of modern-day Nova Scotia is not shown. CNS map no. 245.